Structure of the receptor-activated human TRPC6 and TRPC3 ion channels - Tang, Qinglin; Guo, Wenjun; Zheng, Li; Wu, Jing-Xiang; Liu, Meng; Zhou, Xindi; Zhang, Xiaolin; Chen, Lei (Cell research, 2018)
TRPC6 and TRPC3 are receptor-activated nonselective cation channels that belong to the family of canonical transient receptor potential (TRPC) channels. They are activated by diacylglycerol, a lipid second messenger. TRPC6 and TRPC3 are involved in many physiological processes and implicated in human genetic diseases. Here we present the structure of human TRPC6 homotetramer in complex with a newly identified high-affinity inhibitor BTDM solved by single-particle cryo-electron microscopy to 3.8 Å resolution. We also present the structure of human TRPC3 at 4.4 Å resolution. These structures show two-layer architectures in which the bell-shaped cytosolic layer holds the transmembrane layer. Extensive inter-subunit interactions of cytosolic domains, including the N-terminal ankyrin repeats and the C-terminal coiled-coil, contribute to the tetramer assembly. The high-affinity inhibitor BTDM wedges between the S5-S6 pore domain and voltage sensor-like domain to inhibit channel opening. Our structures uncover the molecular architecture of TRPC channels and provide a structural basis for understanding the mechanism of these channels.